A kind of water-based two-component polyurethane varnish and its preparation process

By using modified acrylic dispersions and modified white carbon black and titanium dioxide in aqueous polyurethane coatings, combined with polyisocyanate curing agent, the drying time, paint film hardness, scratch resistance and oxidation resistance of water-based polyurethane coatings is solved. The shortcomings have achieved higher coating performance and construction flexibility.

CN118725714BActive Publication Date: 2025-02-18ZHONGSHAN UBEST TECH CO LTD

Patent Information

Application Number
CN202410937064.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2025-02-18
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

Water-based polyurethane coatings have shortcomings in terms of drying time, paint film hardness, scratch resistance and oxidation resistance, which limits their construction flexibility and application performance.

Method used

The aqueous polyurethane dispersion and modified acrylic dispersion are used as film forming substances, combined with polyisocyanate as curing agents, and modified white carbon black and modified titanium dioxide are added to improve the coating performance through cross-linking reaction and nanostructure modification.

Benefits of technology

It significantly improves the hardness, wear resistance and oxidation resistance of the paint film, enhances the thermal stability and flame retardant properties of the material, and improves construction flexibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004941657540000021
    Figure BDA0004941657540000021
  • Figure BDA0004941657540000071
    Figure BDA0004941657540000071
Patent Text Reader

Abstract

This invention belongs to the field of coating technology and discloses a water-based two-component polyurethane clear varnish and its preparation process. The water-based two-component polyurethane clear varnish includes component A and component B. Component A includes the following raw materials in parts by weight: 85-110 parts of water-based polyurethane dispersion, 40-45 parts of modified acrylic dispersion, 10-25 parts of modified silica, 30-40 parts of modified titanium dioxide, 4-6 parts of dispersant, 0.5-2 parts of defoamer, 0.5-2 parts of leveling agent, and 10-20 parts of water. Component B is a polyisocyanate curing agent. This invention uses water-based polyurethane dispersion and modified acrylic dispersion as film-forming substances, polyisocyanate as curing agent, and adds modified silica and modified titanium dioxide to prepare a water-based two-component polyurethane clear varnish. The modified acrylic dispersion gives the coating film excellent physical properties such as hardness and gloss. The modified silica can improve the hardness and wear resistance of the coating film, and the modified titanium dioxide can improve the thermal stability and flame retardant properties of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a water-based two-component polyurethane varnish and a preparation process thereof. Background Art

[0002] Water-based paint uses water as a dispersion medium to replace traditional organic solvents, thus achieving a non-toxic, odorless, and pollution-free effect. In recent years, water-based paint has been widely recognized by the market, and its existing problems and accompanying optimal solutions have continued to emerge. In one-component water-based paint, on the one hand, the introduction of hydrophilic groups such as carboxyl and sulfonic acid groups reduces the water resistance and chemical resistance of the coating. On the other hand, the self-crosslinking density is not enough, and the resistance and physical properties have certain defects. Two-component water-based polyurethane coatings, due to chemical cross-linking again during the film-forming process, have better weather resistance and chemical resistance, strong adhesion, wear resistance, high hardness and solvent-based polyurethane coatings, while reducing VOC emissions. Therefore, two-component water-based polyurethane coatings can gradually replace solvent-based coatings in many application fields.

[0003] Two-component waterborne polyurethane coating is a binary glue system with water as the dispersion medium. Due to the "tailorability" of its molecules, combined with new synthesis and cross-linking modification technologies, the composition and structure of the coating can be effectively controlled, making it safe to use, non-toxic, non-flammable, and environmentally friendly. The polyurethane resin molecular structure has hard and soft segment structures, which determines its unique properties of being both hard and flexible. By changing the types and composition ratios of soft and hard segments, waterborne polyurethane products with different properties can be obtained. Its microscopic two-phase structure gives waterborne polyurethane excellent low-temperature film-forming properties, leveling properties and flexibility. However, there are still some problems with waterborne polyurethane, such as the construction limitations caused by seasonal climate due to the drying time of the coating, and the paint film hardness, scratch resistance and oxidation resistance need to be improved. Summary of the invention

[0004] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a water-based two-component polyurethane varnish and a preparation process thereof, using a water-based polyurethane dispersion and a modified acrylic dispersion as film-forming substances, polyisocyanate as a curing agent, and adding modified white carbon black and modified titanium dioxide to prepare a water-based two-component polyurethane varnish.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A water-based two-component polyurethane varnish comprises component A and component B, wherein component A comprises the following raw materials in parts by weight: 85-110 parts of water-based polyurethane dispersion, 40-45 parts of modified acrylic dispersion, 10-25 parts of modified white carbon black, 30-40 parts of modified titanium dioxide, 4-6 parts of dispersant, 0.5-2 parts of defoamer, 0.5-2 parts of leveling agent, and 10-20 parts of water, component B is a polyisocyanate curing agent, the modified acrylic dispersion is a hydroxy acrylic resin dispersion, the modified white carbon black is epoxy-modified polyurethane coated white carbon black, and the modified titanium dioxide is triazine derivative grafted nano titanium dioxide, and the structural formula of the triazine derivative is as follows:

[0007]

[0008] Preferably, the mass ratio of component A to component B is 5 to 8:1.

[0009] Preferably, the dispersant is a modified polyurethane dispersant, the defoamer is a polyether defoamer, an organosilicon defoamer or a polyether siloxane copolymer, and the leveling agent is carboxymethyl cellulose.

[0010] Preferably, the method for preparing the modified acrylic dispersion comprises the following steps:

[0011] A. Add propylene glycol butyl ether and tert-butyl carbonate into the reactor, heat the oil bath to 130-140°C, weigh methacrylic acid, butyl acrylate, hydroxyethyl methacrylate, methacrylic acid and tert-butyl perbenzoate, mix well and slowly drop into the reactor for 3-5 hours. After the dropwise addition is completed, keep the temperature for 1-2 hours to allow the reaction monomers to fully polymerize;

[0012] B. Weigh a small amount of tert-butyl perbenzoate and dissolve it in propylene glycol butyl ether, slowly drop it into the reaction system, keep warm for 1 to 2 hours, then slowly drop the tert-butyl perbenzoate solution, continue to raise the temperature to 145 to 155°C, keep warm for 1 to 2 hours, and obtain a polymer with terminal carboxyl and hydroxyl groups;

[0013] C. Add a certain amount of N,N-dimethylethanolamine to the above polymer while stirring, stir and react for 20-40 minutes, then add water, and then disperse at high speed for 20-40 minutes to obtain a hydroxy acrylic acid dispersion.

[0014] Preferably, the preparation method of modified silica comprises the following steps:

[0015] (1) adding white carbon black to a mixture of anhydrous ethanol and deionized water, stirring and dispersing for 5 to 10 minutes, then adding 3-aminopropyltriethoxysilane to the dispersion of white carbon black, keeping the mixture at 35 to 45° C. for reaction for 1 to 3 hours, filtering, washing, and drying to obtain white carbon black treated with a silane coupling agent;

[0016] (2) vacuum drying poly(1,4-butylene adipate) diol and polypropylene glycol and then adding them to acetone to dissolve to obtain solution A, adding isophorone diisocyanate and dibutyltin dilaurate to acetone to dissolve to obtain solution B, slowly dropping solution A into solution B, and reacting at 50-60° C. for 1-3 hours after the dropping is completed to obtain a polyurethane prepolymer;

[0017] (3) After vacuum drying, E51 epoxy resin is added to a mixture of propylene glycol methyl ether and acetone, and stirred to dissolve, and then dibutyltin dilaurate is added and stirred to obtain a solution C, and the polyurethane prepolymer is added dropwise to the solution C. After the addition is completed, the mixture is reacted at 50 to 60° C. for 1 to 3 hours to obtain an epoxy-modified polyurethane resin;

[0018] (4) The epoxy modified polyurethane resin obtained in step (3) is mixed with an OP emulsifier, and water is added under high-speed stirring at 2000-2500 r / min to obtain an emulsion with a solid content of 35-40%, and then the white carbon black treated with a silane coupling agent in step (1) is added to the emulsion, stirred at 40-50° C. for 20-40 min, and then allowed to stand for 3-5 h, filtered, and dried to obtain modified white carbon black.

[0019] Preferably, the amount of 3-aminopropyltriethoxysilane used in step (1) is 5 to 8% of the mass of white carbon black.

[0020] Preferably, the molar ratio of poly(1,4-butylene adipate) glycol, polypropylene glycol, isophorone diisocyanate and E51 epoxy resin is 3:3:8:1.

[0021] Preferably, the method for preparing modified titanium dioxide comprises the following steps:

[0022] a. Add cyanuric chloride to 1,4-dioxane and triethylamine under nitrogen atmosphere, stir to dissolve cyanuric chloride, then uniformly add 3-aminopropyltriethoxysilane, react in an ice bath for 1-3 hours after the addition is completed, add 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionylhydrazide to the reaction system, then heat up to 40-50°C at a rate of 2-4°C / min, and keep warm for 1-3 hours, finally add 4,4'-dihydroxybenzophenone to the reaction system, heat up to 70-80°C, and keep warm for 1-3 hours, after the reaction is completed, cool and filter to remove triethylamine hydrochloride, remove tetrahydrofuran by vacuum distillation, add ethyl acetate, dry and filter, and vacuum distill the filtrate to obtain a triazine nitrile derivative;

[0023] b. Add nano titanium dioxide powder to a mixture of anhydrous ethanol and deionized water, and disperse it by ultrasonication for 10 to 15 minutes. Adjust the pH value of the solution to 4 with aqueous hydrochloric acid solution, and then slowly add the triazine derivative to the nano titanium dioxide solution, and disperse it by ultrasonication for 5 to 10 minutes. Heat to 60 to 80°C and keep the temperature for reaction for 3 to 5 hours. After cooling, filter, wash and dry to obtain modified titanium dioxide.

[0024] Preferably, the molar ratio of cyanuric chloride, 3-aminopropyltriethoxysilane, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionhydrazide and 4,4'-dihydroxybenzophenone is 1:1:1:1.

[0025] A preparation process of a water-based two-component polyurethane varnish comprises the following steps:

[0026] S1, mixing an aqueous polyurethane dispersion, a modified acrylic dispersion, a dispersant, a defoamer, a leveling agent and water to obtain a mixed solution;

[0027] S2, adding modified white carbon black and modified titanium dioxide into the mixed solution and dispersing them at high speed to obtain a uniform component A;

[0028] S3. Component B is mixed evenly with component A in proportion to obtain a water-based two-component polyurethane varnish.

[0029] Beneficial effects of the present invention:

[0030] The invention uses waterborne polyurethane dispersion and modified acrylic dispersion as film-forming substances, uses polyisocyanate as a curing agent, adds modified white carbon black and modified titanium dioxide, and prepares a waterborne two-component polyurethane varnish, wherein the modified acrylic dispersion contains abundant hydroxyl groups, and the cross-linking reaction of the hydroxyl groups can ensure that the finally formed coating film has excellent physical properties such as hardness and gloss, and the modified white carbon black epoxy-modified polyurethane coating can make the white carbon black uniformly dispersed in the slurry, thereby improving the hardness and wear resistance of the paint film of the material, and the modified titanium dioxide is added to graft nano titanium dioxide with triazine derivatives to functionalize the nano titanium dioxide, thereby improving the thermal stability and flame retardant performance of the material.

[0031] Among them, the modified silica is modified by using a silane coupling agent to modify the surface of the silica to make it rich in amino groups, and then polymerized with an epoxy-modified polyurethane emulsion to form a surface coating on the silica, so that it can be stably dispersed in the water-based two-component polyurethane varnish slurry, thereby improving the wear resistance of the paint surface.

[0032] The modified titanium dioxide uses triazine derivatives grafted onto nano-titanium dioxide. The triazine derivatives contain hindered phenol structure, benzophenone structure and siloxane structure. Both the hindered phenol structure and the benzophenone structure can capture free radicals in the material and decompose hydroperoxides, so that the concentration of free radicals and hydroperoxides in the material remains relatively low, thereby slowing down the reaction rate of chain initiation, chain growth and chain branching of the material, and improving the material's resistance to heat oxidation and light oxidation. After hydrolysis, the siloxane structure bonds with the hydroxyl group on the surface of nano-titanium dioxide, so that the triazine derivatives can be firmly grafted on the surface of nano-titanium dioxide, thereby improving the dispersibility of nano-titanium dioxide in the slurry. At the same time, nano-titanium dioxide itself has ultraviolet shielding function, which can cooperate with hindered phenol and benzophenone to improve the oxidation resistance of the material. In addition, the rich N and Si elements in the triazine derivatives promote the dehydration and carbonization of the polymer during thermal cracking, which can give the material good flame retardant properties. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] A modified acrylic dispersion, wherein the modified acrylic dispersion is a hydroxy acrylic resin dispersion, and a preparation method thereof comprises the following steps:

[0036] A. Add 45g of propylene glycol butyl ether and 5g of tert-butyl carbonate into the reactor, heat the oil bath to 135°C, weigh 28g of methacrylic acid, 45g of butyl acrylate, 5g of hydroxyethyl methacrylate, 15g of methacrylic acid and 3g of tert-butyl perbenzoate, mix well and slowly add dropwise to the reactor for 4h. After the addition is completed, keep warm for 1.5h to allow the reaction monomers to fully polymerize;

[0037] B. Weigh 2 g of tert-butyl perbenzoate and dissolve it in 30 g of propylene glycol butyl ether, slowly drop it into the reaction system, keep the temperature for reaction for 1 hour, then slowly drop the tert-butyl perbenzoate solution, continue to raise the temperature to 150° C., keep the temperature for reaction for 1 hour, and obtain a polymer with terminal carboxyl groups and hydroxyl groups;

[0038] C. Add 15 g of N,N-dimethylethanolamine to the above polymer while stirring, stir and react for 30 minutes, then add 100 mL of water, and then disperse at high speed for 30 minutes to obtain a hydroxy acrylic acid dispersion.

[0039] Example 2

[0040] A modified silica, wherein the modified silica is epoxy-modified polyurethane coated silica, and the preparation method thereof comprises the following steps:

[0041] (1) 10.2 g of white carbon black was added to a mixture of 90 mL of anhydrous ethanol and 10 mL of deionized water, and the mixture was stirred and dispersed for 8 min. Then 1.4 g of 3-aminopropyltriethoxysilane was added to the dispersion of white carbon black, and the mixture was kept at 40° C. for 2 h. After filtering, washing, and drying, white carbon black treated with a silane coupling agent was obtained.

[0042] (2) 11.5 g of poly(1,4-butylene adipate) diol and 0.5 g of polypropylene glycol were vacuum dried and added to 50 mL of acetone to dissolve to obtain solution A; 17.6 g of isophorone diisocyanate and 0.4 g of dibutyltin dilaurate were added to 50 mL of acetone to dissolve to obtain solution B; solution A was slowly added dropwise to solution B; after the addition was completed, the mixture was reacted at 55° C. for 3 h to obtain a polyurethane prepolymer;

[0043] (3) 7.5 g of E51 epoxy resin was vacuum dried and added to a mixture of 25 mL of propylene glycol methyl ether and 25 mL of acetone, and the mixture was stirred to dissolve. Then 0.4 g of dibutyltin dilaurate was added and stirred to obtain a solution C. The polyurethane prepolymer was added dropwise to the solution C. After the addition was completed, the mixture was reacted at 55° C. for 3 h to obtain an epoxy-modified polyurethane resin.

[0044] (4) The epoxy modified polyurethane resin obtained in step (3) is mixed with an OP emulsifier, and water is added under high-speed stirring at 2500 r / min to obtain an emulsion with a solid content of 35%. Then, the white carbon black treated with a silane coupling agent in step (1) is added to the emulsion, stirred at 50° C. for 30 min, and then allowed to stand for 5 h, filtered, and dried to obtain modified white carbon black.

[0045] Example 3

[0046] A modified titanium dioxide, the modified titanium dioxide is a triazine derivative grafted with nano titanium dioxide, the structural formula of the triazine derivative is as follows:

[0047]

[0048] The preparation method of modified titanium dioxide comprises the following steps:

[0049] a. Add 3.7 g of cyanuric chloride to 50 mL of 1,4-dioxane and 20 mL of triethylamine under a nitrogen atmosphere, stir to dissolve the cyanuric chloride, then uniformly drop 4.4 g of 3-aminopropyltriethoxysilane, react in an ice bath for 2 h after the dropwise addition is completed, add 5.8 g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionylhydrazide to the reaction system, then heat to 45°C at a rate of 3°C / min, and keep the temperature for 2 h. Finally, add 4.2 g of 4,4'-dihydroxybenzophenone to the reaction system, heat to 75°C, and keep the temperature for 2 h. After the reaction is completed, cool and filter to remove triethylamine hydrochloride, remove tetrahydrofuran by reduced pressure distillation, then add 50 mL of ethyl acetate, dry and filter, and distill the filtrate under reduced pressure to obtain a triazine nitrile derivative;

[0050] b. Add 4.3 g of nano titanium dioxide powder to a mixture of 40 mL of anhydrous ethanol and 5 mL of deionized water, and disperse by ultrasonication for 12 min. Adjust the pH value of the solution to 4 with aqueous hydrochloric acid solution, and then slowly add 2.5 g of a triazine derivative to the nano titanium dioxide solution, and disperse by ultrasonication for 8 min. Heat to 70 ° C and keep the reaction for 5 h. After cooling, filter, wash, and dry to obtain modified titanium dioxide.

[0051] Example 4

[0052] A water-based two-component polyurethane varnish comprises component A and component B, wherein component A comprises the following raw materials in parts by weight: 85 parts of water-based polyurethane dispersion, 45 parts of modified acrylic dispersion, 10 parts of modified white carbon black, 30 parts of modified titanium dioxide, 4 parts of polyurethane oligomer, 2 parts of polyether defoamer, 0.5 parts of carboxymethyl cellulose, and 20 parts of water, and component B is a polyisocyanate curing agent, and the mass ratio of component A to component B is 5:1. Among them, the modified acrylic dispersion is the hydroxy acrylic resin dispersion prepared in Example 1, the modified white carbon black is the epoxy-modified polyurethane coated carbon black prepared in Example 2, and the modified titanium dioxide is the triazine derivative grafted nano titanium dioxide prepared in Example 3.

[0053] The preparation method of the above-mentioned water-based two-component polyurethane varnish comprises the following steps:

[0054] S1, mixing an aqueous polyurethane dispersion, a modified acrylic dispersion, a polyurethane oligomer, a polyether defoamer, carboxymethyl cellulose and water to obtain a mixed solution;

[0055] S2, adding modified white carbon black and modified titanium dioxide into the mixed solution and dispersing them at high speed to obtain a uniform component A;

[0056] S3. Component B is mixed evenly with component A in proportion to obtain the water-based two-component polyurethane varnish.

[0057] Example 5

[0058] A water-based two-component polyurethane varnish comprises component A and component B, wherein component A comprises the following raw materials in parts by weight: 110 parts of water-based polyurethane dispersion, 40 parts of modified acrylic dispersion, 25 parts of modified white carbon black, 30 parts of modified titanium dioxide, 6 parts of phosphate ester active agent, 0.5 parts of organosilicon defoamer, 2 parts of carboxymethyl cellulose, and 10 parts of water, and component B is a polyisocyanate curing agent, and the mass ratio of component A to component B is 8:1. Among them, the modified acrylic dispersion is the hydroxy acrylic resin dispersion prepared in Example 1, the modified white carbon black is the epoxy-modified polyurethane coated carbon black prepared in Example 2, and the modified titanium dioxide is the triazine derivative grafted nano titanium dioxide prepared in Example 3.

[0059] The preparation method of the above-mentioned water-based two-component polyurethane varnish comprises the following steps:

[0060] S1, mixing an aqueous polyurethane dispersion, a modified acrylic dispersion, a phosphate ester active agent, an organosilicon defoamer, carboxymethyl cellulose and water to obtain a mixed solution;

[0061] S2, adding modified white carbon black and modified titanium dioxide into the mixed solution and dispersing them at high speed to obtain a uniform component A;

[0062] S3. Component B is mixed evenly with component A in proportion to obtain the water-based two-component polyurethane varnish.

[0063] Example 6

[0064] A water-based two-component polyurethane varnish comprises component A and component B, wherein component A comprises the following raw materials in parts by weight: 95 parts of water-based polyurethane dispersion, 42 parts of modified acrylic dispersion, 16 parts of modified white carbon black, 25 parts of modified titanium dioxide, 5 parts of polyurethane oligomer, 1.2 parts of polyether siloxane copolymer, 1 part of carboxymethyl cellulose, and 15 parts of water, and component B is a polyisocyanate curing agent, and the mass ratio of component A to component B is 6:1. Among them, the modified acrylic dispersion is the hydroxy acrylic resin dispersion prepared in Example 1, the modified white carbon black is the epoxy-modified polyurethane coated carbon black prepared in Example 2, and the modified titanium dioxide is the triazine derivative grafted nano titanium dioxide prepared in Example 3.

[0065] The preparation method of the above-mentioned water-based two-component polyurethane varnish comprises the following steps:

[0066] S1, mixing an aqueous polyurethane dispersion, a modified acrylic dispersion, a polyurethane oligomer, a polyether siloxane copolymer, carboxymethyl cellulose and water to obtain a mixed solution;

[0067] S2, adding modified white carbon black and modified titanium dioxide into the mixed solution and dispersing them at high speed to obtain a uniform component A;

[0068] S3. Component B is mixed evenly with component A in proportion to obtain the water-based two-component polyurethane varnish.

[0069] Comparative Example 1

[0070] A water-based two-component polyurethane varnish comprises component A and component B, wherein component A comprises the following raw materials in parts by weight: 95 parts of water-based polyurethane dispersion, 16 parts of modified white carbon black, 25 parts of modified titanium dioxide, 5 parts of polyurethane oligomer, 1.2 parts of polyether siloxane copolymer, 1 part of carboxymethyl cellulose, and 15 parts of water, and component B is a polyisocyanate curing agent, and the mass ratio of component A to component B is 6:1. Among them, the modified white carbon black is the epoxy-modified polyurethane coated carbon black prepared in Example 2, and the modified titanium dioxide is the triazine derivative grafted nano titanium dioxide prepared in Example 3.

[0071] The preparation method of the above-mentioned water-based two-component polyurethane varnish comprises the following steps:

[0072] S1, mixing an aqueous polyurethane dispersion, a polyurethane oligomer, a polyether siloxane copolymer, carboxymethyl cellulose and water to obtain a mixed solution;

[0073] S2, adding modified white carbon black and modified titanium dioxide into the mixed solution and dispersing them at high speed to obtain a uniform component A;

[0074] S3. Component B is mixed evenly with component A in proportion to obtain the water-based two-component polyurethane varnish.

[0075] Comparative Example 2

[0076] A water-based two-component polyurethane varnish comprises component A and component B, wherein component A comprises the following raw materials in parts by weight: 95 parts of water-based polyurethane dispersion, 42 parts of modified acrylic dispersion, 25 parts of modified titanium dioxide, 5 parts of polyurethane oligomer, 1.2 parts of polyether siloxane copolymer, 1 part of carboxymethyl cellulose, and 15 parts of water, and component B is a polyisocyanate curing agent, and the mass ratio of component A to component B is 6:1. Among them, the modified acrylic dispersion is the hydroxy acrylic resin dispersion prepared in Example 1, and the modified titanium dioxide is the triazine derivative grafted nano titanium dioxide prepared in Example 3.

[0077] The preparation method of the above-mentioned water-based two-component polyurethane varnish comprises the following steps:

[0078] S1, mixing an aqueous polyurethane dispersion, a modified acrylic dispersion, a polyurethane oligomer, a polyether siloxane copolymer, carboxymethyl cellulose and water to obtain a mixed solution;

[0079] S2, adding the modified titanium dioxide into the mixed solution and dispersing at high speed to obtain a uniform component A;

[0080] S3, component B is mixed evenly with component A in proportion to obtain the water-based two-component polyurethane varnish comparative example 3

[0081] A water-based two-component polyurethane varnish comprises component A and component B, wherein component A comprises the following raw materials in parts by weight: 95 parts of water-based polyurethane dispersion, 42 parts of modified acrylic dispersion, 16 parts of modified white carbon black, 5 parts of polyurethane oligomer, 1.2 parts of polyether siloxane copolymer, 1 part of carboxymethyl cellulose, and 15 parts of water, and component B is a polyisocyanate curing agent, and the mass ratio of component A to component B is 6:1. Among them, the modified acrylic dispersion is the hydroxyl acrylic resin dispersion prepared in Example 1, and the modified white carbon black is the epoxy-modified polyurethane coated carbon black prepared in Example 2.

[0082] The preparation method of the above-mentioned water-based two-component polyurethane varnish comprises the following steps:

[0083] S1, mixing an aqueous polyurethane dispersion, a modified acrylic dispersion, a polyurethane oligomer, a polyether siloxane copolymer, carboxymethyl cellulose and water to obtain a mixed solution;

[0084] S2, adding modified silica to the mixed solution and dispersing at high speed to obtain a uniform component A;

[0085] S3. Component B is mixed evenly with component A in proportion to obtain the water-based two-component polyurethane varnish.

[0086] Performance Testing

[0087] 1. The pencil hardness of the paint film prepared in Examples 3 to 6 and Comparative Examples 1 to 2 was measured according to GBT 6739-2022, the impact resistance of the paint film was measured according to GB / T 1732-2020, the adhesion of the paint film was measured according to GB / T 9286-2021, and the wear resistance of the paint film was tested according to GB / T 1768-2006. The data are shown in Table 1 below.

[0088] Table 1 Physical and chemical properties of water-based two-component polyurethane varnish

[0089]

[0090] From the data in Table 1, it can be seen that in Comparative Example 1, no modified acrylic dispersion was added, and its adhesion and wear resistance were slightly reduced. In Comparative Examples 2 and 3, no modified white carbon black and modified titanium dioxide were added, and the hardness and impact resistance of the paint film were reduced, but the adhesion was not greatly affected. Among them, the reduction in Comparative Example 2 was the most obvious, and the loss of mass during the wear test was also large. It can be seen that adding modified white carbon black can significantly improve the wear resistance of water-based two-component polyurethane varnish. The wear resistance in Comparative Example 3 is slightly weaker than that in Examples 3 to 4, which is due to the lack of modified titanium dioxide, and modified titanium dioxide also has a reinforcing effect.

[0091] 2. Aging resistance test

[0092] The water-based two-component polyurethane varnishes prepared in Examples 3 to 6 and Comparative Examples 1 to 2 were subjected to artificial weathering tests according to GB / T1865-2009 and evaluated according to GB / T1766-2008. At the same time, the vertical burning grade (UL94) was tested according to ASTM3801 standard, and the data obtained are shown in Table 2 below.

[0093] Table 2 Aging resistance of water-based two-component polyurethane varnish

[0094]

[0095] It can be seen from the data in Table 2 that in Example 2, no modified titanium dioxide was added, and the paint film had obvious bubbling and peeling after artificial weathering, and severe powdering. The weather resistance was significantly lower than that of other groups, and the flame retardant performance was also worse than that of other groups, indicating that the modified titanium dioxide had a good anti-aging and flame retardant effect.

[0096] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A water-based two-component polyurethane varnish, characterized in that: The invention comprises component A and component B, wherein component A comprises the following raw materials in parts by weight: 85-110 parts of waterborne polyurethane dispersion, 40-45 parts of modified acrylic dispersion, 10-25 parts of modified white carbon black, 30-40 parts of modified titanium dioxide, 4-6 parts of dispersant, 0.5-2 parts of defoamer, 0.5-2 parts of leveling agent, and 10-20 parts of water; component B is a polyisocyanate curing agent, the modified acrylic dispersion is a hydroxy acrylic resin dispersion, the modified white carbon black is epoxy-modified polyurethane coated white carbon black, and the modified titanium dioxide is triazine derivative grafted nano titanium dioxide, and the structural formula of the triazine derivative is as follows: ; The preparation method of the modified titanium dioxide comprises the following steps: a. Add cyanuric chloride to 1,4-dioxane and triethylamine under nitrogen atmosphere, stir to dissolve cyanuric chloride, then uniformly add 3-aminopropyltriethoxysilane, react in an ice bath for 1-3 hours after the addition is completed, add 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionylhydrazide to the reaction system, then heat up to 40-50°C at a rate of 2-4°C / min, and keep warm for 1-3 hours, finally add 4,4'-dihydroxybenzophenone to the reaction system, heat up to 70-80°C, and keep warm for 1-3 hours, after the reaction is completed, cool and filter to remove triethylamine hydrochloride, remove tetrahydrofuran by vacuum distillation, add ethyl acetate, dry and filter, and vacuum distill the filtrate to obtain a triazine nitrile derivative; b. Add nano titanium dioxide powder to a mixture of anhydrous ethanol and deionized water, and perform ultrasonic dispersion for 10-15 minutes. Use hydrochloric acid aqueous solution to adjust the pH value of the solution to 4. Then slowly add the triazine derivative to the nano titanium dioxide solution, and perform ultrasonic dispersion for 5-10 minutes. Heat to 60-80°C and keep the temperature for reaction for 3-5 hours. After cooling, filter, wash, and dry to obtain modified titanium dioxide. The molar ratio of cyanuric chloride, 3-aminopropyltriethoxysilane, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionylhydrazide and 4,4'-dihydroxybenzophenone is 1:1:1:1; the preparation method of the modified acrylic dispersion comprises the following steps: A. Add propylene glycol butyl ether and tert-butyl carbonate into the reactor, heat the oil bath to 130-140°C, weigh methacrylic acid, butyl acrylate, hydroxyethyl methacrylate, methacrylic acid and tert-butyl perbenzoate, mix well and slowly drop into the reactor for 3-5 hours. After the dropwise addition is completed, keep the temperature for 1-2 hours to allow the reaction monomers to fully polymerize; B. Weigh a small amount of tert-butyl perbenzoate and dissolve it in propylene glycol butyl ether, slowly drop it into the reaction system, keep the temperature for reaction for 1-2 hours, then slowly drop the tert-butyl perbenzoate solution, continue to raise the temperature to 145-155°C, keep the temperature for reaction for 1-2 hours, and obtain a polymer with terminal carboxyl and hydroxyl groups; C. Add a certain amount of N,N-dimethylethanolamine to the above polymer while stirring, stir and react for 20-40 minutes, then add water, and then disperse at high speed for 20-40 minutes to obtain a hydroxy acrylic acid dispersion; The preparation method of the modified white carbon black comprises the following steps: (1) Add white carbon black to a mixture of anhydrous ethanol and deionized water, stir and disperse for 5 to 10 minutes, then add 3-aminopropyltriethoxysilane to the dispersion of white carbon black, keep warm at 35 to 45°C for 1 to 3 hours, filter, wash and dry to obtain white carbon black treated with a silane coupling agent; (2) After vacuum drying, poly(1,4-butylene adipate) diol and polypropylene glycol are added to acetone to dissolve to obtain solution A, and isophorone diisocyanate and dibutyltin dilaurate are added to acetone to dissolve to obtain solution B. Solution A is slowly added dropwise to solution B. After the addition is completed, the mixture is reacted at 50-60° C. for 1-3 hours to obtain a polyurethane prepolymer; (3) After vacuum drying, the E51 epoxy resin is added to a mixture of propylene glycol methyl ether and acetone and stirred to dissolve, and then dibutyltin dilaurate is added and stirred to obtain a solution C. The polyurethane prepolymer is added dropwise to the solution C. After the addition is completed, the mixture is reacted at 50-60°C for 1-3 hours to obtain an epoxy-modified polyurethane resin; (4) The epoxy modified polyurethane resin obtained in step (3) is mixed with an OP emulsifier, and water is added under high-speed stirring at 2000-2500 r / min to obtain an emulsion with a solid content of 35-40%. Then, the white carbon black treated with a silane coupling agent in step (1) is added to the emulsion, stirred at 40-50° C. for 20-40 min, and then allowed to stand for 3-5 h, filtered, and dried to obtain the modified white carbon black.

2. The water-based two-component polyurethane varnish according to claim 1, characterized in that: The mass ratio of component A to component B is 5-8:

1.

3. The water-based two-component polyurethane varnish according to claim 1, characterized in that: The dispersant is a polyurethane oligomer or a phosphate ester active agent, the defoamer is a polyether defoamer, an organosilicon defoamer or a polyether siloxane copolymer, and the leveling agent is carboxymethyl cellulose.

4. The water-based two-component polyurethane varnish according to claim 1, characterized in that: The amount of 3-aminopropyltriethoxysilane used in step (1) is 5-8% of the mass of white carbon black.

5. The water-based two-component polyurethane varnish according to claim 1, characterized in that: The molar ratio of the poly(1,4-butylene adipate) glycol, polypropylene glycol, isophorone diisocyanate and E51 epoxy resin is 3:3:8:

1.

6. A process for preparing the water-based two-component polyurethane varnish according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, mixing an aqueous polyurethane dispersion, a modified acrylic dispersion, a dispersant, a defoamer, a leveling agent and water to obtain a mixed solution; S2, adding modified white carbon black and modified titanium dioxide into the mixed solution and dispersing them at high speed to obtain a uniform component A; S3. Component B is mixed evenly with component A in proportion to obtain the water-based two-component polyurethane varnish.

Citation Information

Patent Citations

  • Two-component water-based varnish for new energy automobile as well as preparation method and application of two-component water-based varnish

    CN116144253A

  • Environment-friendly fireproof wear-resistant silicon glaze floor material and preparation process thereof

    CN117986968A

Cited By

  • Waterborne acrylic polyurethane paint and preparation method thereof

    CN122146152A

  • A waterborne acrylic polyurethane paint and a preparation method thereof

    CN122146152B